Negotiating Teacher Professional Identity and Agency in the Era of AI: Evidence from Faith-based Educational Institutions through a Delphi Inquiry - Ma'mun, Nadiah; Riyono, Ahdi; Mariam, Siti (Journal of English Teaching and Learning Issues, 2025)
Teacher professional identity and agency play crucial roles in shaping educational practices, particularly in faith-based education, where values, beliefs, and institutional expectations intersect. This study employs the Delphi method to explore the perspectives of educators, administrators, and scholars on the formation and enactment of teacher identity and agency within faith-based educational settings. Through iterative rounds of expert input, key themes emerge, including the influence of religious doctrine on pedagogical decisions, the negotiation of personal and institutional values, and the role of community engagement in reinforcing professional identity. The findings highlight the dynamic, context-dependent nature of teacher agency, underscoring the need for supportive institutional structures that foster autonomy while maintaining alignment with faith-based principles. This research contributes to a deeper understanding of how educators navigate their professional roles within religious educational contexts, offering insights for policy and teacher development programs.